2011
DOI: 10.4238/2011.december.12.4
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of worldwide Jerusalem artichoke (Helianthus tuberosus) germplasm as revealed by RAPD markers

Abstract: ABSTRACT. Jerusalem artichoke (Helianthus tuberosus) is a wild relative of the cultivated sunflower (H. annuus); it is an old tuber crop that has recently received renewed interest. We used RAPD markers to characterize 147 Jerusalem artichoke accessions from nine countries. Thirty RAPD primers were screened; 13 of them detected 357 reproducible RAPD bands, of which 337 were polymorphic. Various diversity analyses revealed several different patterns of RAPD variation. More than 93% of the RAPD variation was fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…This assessment relied upon the examination of each genotype and use of the simple matching coefficient (S) (Sokal and Michener, 1958). The dissimilarity (D) observed at each loci was denoted as 1 -S, so that a measure of the mean dissimilarity among the genotypes could be obtained by taking an average of all the n -1 EST-SSR dissimilarities (AD) associated with each genotype (Wangsomnuk et al, 2011b). Allelic diversity for each loci was quantified using the concept of polymorphism information content (PIC) described by Botstein et al (1980), whose equation held that PIC = 1 -( ) ∑ 2 ij P when P ij is the frequency of the j th allele of the i th locus.…”
Section: Discussionmentioning
confidence: 99%
“…This assessment relied upon the examination of each genotype and use of the simple matching coefficient (S) (Sokal and Michener, 1958). The dissimilarity (D) observed at each loci was denoted as 1 -S, so that a measure of the mean dissimilarity among the genotypes could be obtained by taking an average of all the n -1 EST-SSR dissimilarities (AD) associated with each genotype (Wangsomnuk et al, 2011b). Allelic diversity for each loci was quantified using the concept of polymorphism information content (PIC) described by Botstein et al (1980), whose equation held that PIC = 1 -( ) ∑ 2 ij P when P ij is the frequency of the j th allele of the i th locus.…”
Section: Discussionmentioning
confidence: 99%
“…JA breeding programs were largely based on the intra-specific hybridization associated with low seed set, resulting in moderate success in creation of new diversity. The inter-specific hybridization of JA with other Helianthus species should be preferred instead [48,59]. Strategy of using related species to introgress useful gene variants is commonly used also in other polyploids e.g., wheat [60,61], canola [62] or cotton [63].…”
Section: Genetic Resourcesmentioning
confidence: 99%
“…Recently, Puttha et al [14] reported genetic variability for qualitative and quantitative traits among 79 Jerusalem artichoke accessions, and Sennoi et al [15] evaluated 91 Jerusalem artichoke genotypes related to tolerance to diseases and lesions, days to permanent wilting, plant height, and shoot and root dry weight under greenhouse conditions. Wangsomnuk et al [16] used Random Amplified Polymorphic DNA (RAPD) markers to characterize 147 Jerusalem artichoke accessions from nine countries; 30 RAPD primers were screened. Furthermore, 357 reproducible RAPD bands were detected in the 13 RAPD primers, of which 337 were polymorphic, providing useful diversity information for understanding the Jerusalem artichoke gene pool and genetic improvements.…”
Section: Genetic Resourcesmentioning
confidence: 99%